Software-based attendance system using web technology - Mohamed Shahrul Bin Mohamed Subuhan (2023)
Attendance is one of the important factors in school, college and in university. The attendance plays an important role in passing the subject since the students must possess at least 80% of the attendance. Still most of the educational institute using only the paper-based attendance system which is not an effective way in both time management and work management. I have a suggested a better way of taking attendance which doesn’t use any paper, biometrics, cards etc. and it is fully a software-based application. Since now electronic devices become a part of every individual it is easy when there is an app to manage our work. In this context, I have proposed an alternative method of taking attendance using web-based software application. Since it is web-based application it requires internet browser to run the application. Internet browser is one on the preinstall apps in every smart mobile phone. So, no need of any extra apps to be installed in order to use this application. The app can run in any device with internet browser on it i.e. it can be run on desktop, tablet and mobile phones. The working app is so simple. Students just need to click on their name once they enter class where the device is placed on a table.